MENENTUKAN POLA PEGAWAI HONORER DI DINAS PERUMAHAN KAWASAN PEMUKIMAN DAN PERTANAHAN DALAM PENERAPAN METODE K-MEANS - Alinse, Rizka Tri; Sari, Venny Novita; Sallaby, Achmad Fikri (Jurnal Media Infotama, 2021)
The Housing, Settlement Areas and Land Service of Bengkulu Province is a government agency in Bengkulu Province. Performance assessment using a predetermined form. This agency has 11 honorary employees. Every year an evaluation of the performance of honorary employees will be carried out to make decisions and consideration for honorary employee contracts. The aim of this research was to apply the K-Means Method to determine the pattern of honorary employees in the Housing, Settlement and Land Service of Bengkulu Province and to create an application that could provide information on the pattern of honorary employees in the Housing, Settlement and Land Service of Bengkulu Province. The application of the K-Means Method in determining the Pattern of Honorary Employees in the Housing, Settlement and Land Services Department of Bengkulu Province was made using the Visual Basic .Net programming language and SQL Server 2008 Database. The grouping of honorary employee data is based on the results of performance assessments that have been carried out, which in this case There are two to four groups that can be used to differentiate between one honorary employee and another. The results of this grouping can later be used as consideration for the Bengkulu Province Housing, Settlement and Land Services Department to determine who will be contracted for the following year. Based on the results of the tests that have been carried out, the application in determining the pattern of honorary employees can provide information to the Housing, Settlement and Land Services Department of Bengkulu Province as to who is eligible to be given a new contract from the results of grouping performance assessment data for honorary employees.